Rare Case of Intraocular Dirofiliariosis. Surgical Removing Method - V. N. Kazaykin; A. V. Guryev; A. V. Lizunov; D. A. Mazein (Oftalʹmologiâ, 2019)
Dirofilariasis is a biohelminthiasis characterized by damage to the hypodermis, less often than internal organs, in about 50 % of cases localized under the eye membranes, adnexa or in the orbit; the clinical symptoms depend on the location of the parasite infestation. This is a serious disease that can cause dangerous somatic complications. Currently, there is an increase in the incidence of dirofilariasis and the “expansion” of its endemic zones to the north. Most often, the parasite develops at the site of a mosquito bite — subcutaneously, it determines the subsequent clinical manifestations. A lot of questions cause the development of the nematode in the internal structures of the eye, as well as the pathway of penetration of the parasite. The literature describes isolated cases of intraocular invasion of dirofilariae, for example, in Russia since 1972, only three such cases have been recorded. This article presents a clinical case of intravitreal dirofilariasis and presents a method for its surgical treatment. Currently, there is no single approach to removing dirofilaria from the vitreous cavity due to the rare occurrence of this pathology. The high probability of the inflammatory reaction associated with the presence of the xenoagent, its fragmentation during the manipulation, as well as the potential decrease in visual acuity, determined the purpose of this work — to develop a method for surgical removal of the worm from the eye cavity in intact form using a closed manual aspiration system via 2-port access 25G without vitrectomy for further identification in the parasitological department of the clinical diagnostic laboratory.